College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 1, Equations and Graphs - Section 1.4 - Solving Quadratic Equations - 1.4 Exercises - Page 123: 42



Work Step by Step

We solve using the quadratic formula: $3+5z+z^{2}=0$ $z^{2}+5z+3=0$ $z=\frac{-b\pm\sqrt{b^{2}-4ac}}{2a}=\frac{-(5)\pm\sqrt{(5)^{2}-4(1)(3)}}{2(1)}=\frac{-5\pm\sqrt{25-12}}{2}=\frac{-5\pm\sqrt{13}}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.